REPRODUCTIVE AND SOMATIC HEALTH OF ADOLESCENT GIRLS IN THE SETTING OF PREVENTIVE EDUCATIONAL SUPPORT: RESULTS OF A PROSPECTIVE STUDY - Makarov, Konstantin Yurievich; Sokolova, Tatiana Mikhailovna; Kuleshov, Vitaly Mikhailovich; Lukasheva, Olga Vladimirovna (Mother and Baby in Kuzbass, 2026)
The aim of the research – to assess reproductive and somatic health in adolescent girls from Novosibirsk and the Novosibirsk Region during prospective follow-up and to evaluate its association with preventive educational intervention.Materials and methods. This prospective study included 550 adolescent girls referred to a gynecologist; 481 completed follow-up. The main group comprised 210 patients who used materials from an electronic school of reproductive health, while the control group included 271 patients without preventive intervention. Assessment was performed at baseline before the age of 16 years and repeated at the age of 16-18 years. Menstrual characteristics, gynecological and somatic morbidity, and sexual and contraceptive behavior were analyzed.Results. At baseline, the groups were comparable in age, age at menarche, and prevalence of gynecological disorders. Gynecological pathology was detected in 41.9% of the main group and 42.4% of the control group; somatic disorders were found in 26.2% and 31.0%, respectively. By the second visit, the prevalence of both gynecological and somatic pathology increased in both groups; however, the intervention group demonstrated more favorable menstrual outcomes. The odds of irregular menstruation were 2.17 times lower, while the probability of dysmenorrhea was 1.6 times higher in the control group. Inflammatory reproductive disorders, higher sexual activity, and lower adherence to regular contraceptive use were more common in controls.Conclusions. Remote preventive educational support using an electronic school of reproductive health was associated with a more favorable course of selected reproductive health indicators in adolescent girls and may be considered a promising adjunct to preventive care.
Keywords: adolescent girls; reproductive health; somatic health; menstrual function; prevention of gynecological diseases; reproductive behavior